ANALYZING INDONESIAN ONLINE NEWSPAPER HEADLINES USING LEXICAL FUNCTIONAL GRAMMAR - Purwanti, Annisa Ratna (Universitas Pendidikan Indonesia, 2019)
Newspaper headlines have different characteristics to daily or ordinary sentences. They are constructed in such a way to make the readers interested to read the whole news articles. As a result, the syntax for headlines is different. The omission of some parts of the sentences in the headlines are one of the strategies held by the writers to construct effiecient and effective headlines due to the limited space given. Therefore, this qualitative study aims to highlight the syntactical structures of headlines, and also to explain the functions of the words found in the headlines using Lexical Functional Grammar (LFG). In the analysis, LFG has two structures; c-structure and f-structure. C-structure is represented by X-bar in the form of tree diagram, while f-structure is represented by a matrix and followed by a lexical entry. The findings show that there are several characteristics of several famous Indonesian online newspaper headlines which can be a generic structure of a headline. The use of X-COMP, X-ADJ, and OBLÎ¸ tends often to occur in the Indonesian headlines. By implementing these functions, it can be a strategy for the writers in generating catchy and efficient headlines.Â